Literature Review of Wireless Power Transfer Technology for Electric Vehicle Battery Charging - Kim, Dowon (2017)
To achieve the reduction of the carbon dioxide emission and the consumption of fossil fuel, electric vehicles(EVs) have emerged as a great solution with the enthusiastic supports from the governments of many countries. As the demand of EVs increases, an efficient and safe battery charging device is required. The charging system with a wireless power transfer (WPT) device provides a simpler way of charging a battery than a plug-in system which is currently dominating the EV market. Furthermore, WPT technologies facilitate the dynamic battery charging on the road during driving or stopping. In the recent WPT systems, the efficiency presents over 90% and the level of few kilowatts electric power is transferred to the distance of tens of centimetres. Therefore, it is expected that further WPT charging systems are to be equipped on EVs for reducing the battery weight and the frequent charging. This paper introduces the different technologies of the WPT charging systems: inductive power transfer, capacitive power transfer and microwave power transfer. In addition, the state of the art for contactless battery charging systems of EVs is also reviewed under two conditions of the vehicle: parking or driving state in several types of transportations.Then the current studies for enhancing the performance of the WPT EV charging system are reviewed in four categories: DC-HF AC inverter with controller, coupling topologies, voltage regulation with load and safety.